Diagnostic value of ileocolic artery and vein diameters in acute appendicitis - Davut Unsal Capkan (Medicine, 2026)
Acute appendicitis is a common surgical emergency characterized by right lower quadrant pain. This study investigated the diagnostic value of ileocolic artery (ICA) and ileocolic vein (ICV) diameters measured using contrast-enhanced computed tomography (CT) in patients with suspected acute appendicitis. This retrospective observational study included 203 patients aged 18 to 70 years who underwent CT for abdominal pain between January 2022 and December 2024, comprising 97 patients with acute appendicitis and 106 controls. ICA and ICV diameters were measured within the proximal 3 cm segments arising from the superior mesenteric vessels. Data were analyzed using the Mann–Whitney U test, receiver operating characteristic analysis, and multivariable logistic regression. The appendicitis group had significantly larger ICA and ICV diameters than the control group (ICA: 2.86 ± 0.43 mm vs 2.03 ± 0.48 mm; ICV: 4.56 ± 0.72 mm vs 3.58 ± 0.66 mm; both P < .001). ICA diameter showed an area under the curve of 0.915 at a cut-off value of 2.25 mm, with 95.9% sensitivity and 75.5% specificity, whereas ICV diameter showed an area under the curve of 0.854 at a cut-off value of 4.05 mm, with 81.4% sensitivity and 77.4% specificity. Multivariable logistic regression identified both ICA and ICV diameters as independent predictors of acute appendicitis (ICA: odds ratio = 26.78, 95% confidence interval: 9.91–86.72; ICV: odds ratio = 8.38, 95% confidence interval: 3.83–20.63). ICA and ICV diameter measurements may provide objective and quantitative adjunctive markers for diagnosing acute appendicitis but should be interpreted alongside conventional CT findings and clinical evaluation.